JSVM reference software - Maarif, Haris Al Qodri; Gunawan, Teddy Surya; Khalifa, Othman Omran (IIUM Press, 2011)
There are some video standards that are used in the digital life. The video standard is used for respective purposes such as storage, video streaming, or video transmission. In order to encode the video files into some specific standard video, the video encoder software is required to perform the video processing. For the well-established video coding standard, the video encoder software is coming on ready used software packages. But for SVC, as an ongoing video standard, the available encoder software is the reference software which can be modified and tested